The stereodivergent asymmetric synthesis of a range of 2-(1 '-hydroxyalkyl)phenols - Davies, S; Hume, W; Roberts, P; Thomson, J (2010)
The use of the (S)-α-methylbenzyl group as a chiral auxiliary has allowed the diastereoselective ortho-deprotonation of a chromium tricarbonyl complexed phenoxy ring. When the resultant ortho-anion is treated with an aldehyde two diastereoisomeric complexes are formed, in relatively poor dr, which differ in the configuration of the newly formed benzylic stereogenic centre. However, both ortho-formylation followed by treatment with Grignard reagents and ortho-acylation followed by reduction with Super-Hydride® were found to be completely diastereoselective, giving access to either epimer of the corresponding benzylic alcohol complexes in >99:1 dr. Subsequent oxidative removal of the chromium tricarbonyl unit, followed by cleavage of the O-α-methylbenzyl chiral auxiliary gives enantiopure 2-(1′- hydroxyalkyl)phenols. Following this stereodivergent procedure, either enantiomer of the product may be accessed from a single antipode of [(α-methylbenzyloxy)benzene]Cr(CO)3. © 2010 Elsevier Ltd.